Durabilitas Campuran Stone Matrix Asphalt Kasar Menggunakan Limbah Gypsum Sebagai Substitusi Filler - Deyana Shentikhe Batara Musu’; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
In fact, most of the construction of road pavement layers is damaged due to rainwater puddles. This study was intended to determine the durability of the Coarse Stone Matrix Asphalt mixture using gypsum waste as a filler substitution. The results of research, through the marshall immersion test with the proportion of gypsum waste as a cement filler substitution, namely 25%: 75% with 6% asphalt content and variations in immersion time, namely 12 hours, 24 hours. 36 hours, 48 hours, and 60 hours. The test results for the Coarse Asphalt Stone Matrix mixture obtained durability between 97.99% - 92.31%. The relative durability value decreases with increasing immersion time, due to a large number of cavities or pores of the mixture filled with water so that the mixture is easily damaged.